FUNDAMENTAL PRINCIPLES IN TEACHING THE SCIENCE OF MATERIALS SCIENCE AND CONSTRUCTION MATERIALS TECHNOLOGY (American Journal of Pedagogical and Educational Research, 2025)
Fundamental principles are the basis for teaching "Materials science and technology of construction materials" in higher education. Because mastering the fundamental principles and the scientific and technical theory based on it - the perfect understanding of the physical rules of technique and technology, as well as the nature of teaching special subjects, creates an opportunity to creatively solve issues and problems. The application of the principle of fundamentals in the process of training engineers can have a good effect in a rational combination of fundamental, general technical and special training components.